AESTHETICS AND IMPLICATIONS OF HADOTI SCHOOL OF PAINTING: AN EVALUATIVE ANALYSIS OF VIBRANT REFLECTION OF THE RAJPUT STYLE OF PAINTING - Nogia, Harshita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This forum explores the ways in which the Hadoti School of Painting, more than other forms of art, reflects the love of chromatic expression. Hadoti paintings, which are known for their strong lines and vibrant colours, effectively contrast with the vigor and strength of Rajasthani paintings' characterization. Rajasthan's topography is characterised by dramatic contrasts, from the wealthy black soil and environment of Malwa to the river Chambal, the verdant eastern region, and the nearly unending dry desert of Western Rajasthan. These landscapes are strikingly colourful and fascinating. The brave and courageous people of Rajasthan have always maintained their resilient spirit despite living in a place with harsh weather and geographical conditions. For Rajasthanis, colour is an integral aspect of daily existence. The tone is an important symbol of the rigorous spirit in its arts and architecture, in its clothing and costumes, and in its rites and rituals. Perhaps Hadoti has a distinct style but the common trait is, it called Rajasthan Style of painting constructs Rajasthan as rich in colour and united with culture.